Detecting and Preventing Defensive Reactions Toward Persuasive Information on Fruit and Vegetable Consumption Using Induced Eye Movements - Dijkstra, Arie; Elbert, Sarah P. (Frontiers in Psychology, 2021)
Objective. Persuasive messages regarding fruit and vegetable consumption often meet defensive reactions from recipients, which may lower message effectiveness. Individual differences in emotion-regulation and gender are expected to predict these reactions. In the Working Memory Account of Persuasion, inducing voluntary eye movements during the processing of the auditory persuasive information might prevent defensiveness and, thereby, increase message effectiveness. Methods. Participants in two independently recruited samples from the general population (N=118 and N=99) listened to a negatively framed auditory persuasive message advocating fruit and vegetable consumption. Half of them were asked to keep following a regularly moving stimulus on their screen with their eyes. At pretest, the individual difference of cognitive self-affirmation inclination (CSAI) and gender were assessed to predict defensive reactions. Results. In Study 1, induced eye-movements significantly increased self-reported consumption after two weeks when CSAI was low, but only in males, as indicated by a significant three-way interaction (p<.001). With negative self-evaluative emotions as dependent variable this three-way interaction was also significant (p<.05), suggesting that induced eye-movements prevented defensiveness in low CSAI males. Study 2 did not assess consumption but replicated the latter three-way interaction (p<.05). Conclusions. The studies replicated our earlier findings regarding the moderating effects of individual differences in emotion-regulation (i.e., CSAI) on persuasion but they also revealed gender differences in persuasion that are related to the working memory. The Working Memory Account of Persuasion provides new theoretical as well as practical angles on persuasion to target individuals in persuasion to increase fruit and vegetable consumption.